(untitled) (Historia, 2021)
The nineteenth century saw a considerable expansion f Europeansettlement in Australasia, southern Mrica and North America. All areof great interest politically, socially and economically, but for the studentof constitutional development the southern Mrican movement is of possiblyunique interest. The American, the Australian or the New Zealandertook his accepted constitutional forms and practices with him, but theVoortrekkers left in search of independence, seeking escape from politicalpractices and theories of which they disapprovea. In other words thoseother pioneers advanced their frontiers, while the Trekkers broke throughtheir’s, intent on preserving the old ways on the other side. They there-fore had to erect their own constitutional establishments, starting verynearly from scratch as far as the central government was concerned,though they were better placed as regards local government, having hadsome first hand experience of the Cape’s system. It is in the uniquenature of their movement and the fact that they were not over well equippedfor their self imposed task that the major interest in studying their actionslies